Enhancing Climate Resilience in Tank Irrigation Systems: Challenges and Adaptive Strategies - Malaisamy, A.; Rithika, S.; Raswanthkrishna, M. (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
Disrupting water resources and rainfall patterns, climate change creates a wide range of challenges that are changing hydrological systems around the globe. Tank irrigation systems have historically been critical in semiarid and rural regions for capturing and storing rainwater for agriculture, groundwater recharge and rural livelihoods. Tank irrigation systems, crucial for global food security, face significant threats from climate change, including rising temperatures, altered precipitation patterns, and increased extreme weather events that impact water availability, compromising ecosystem conservation and agricultural productivity. This review article examines key strategies to enhance resilience in tank irrigation systems to address these challenges, ensuring sustainable development. Climate change impacts urban communities and presents unique challenges resembling mountains, where steep slopes and erratic precipitation patterns exacerbate soil erosion and hinder water dilution. Effective strategies to address these issues include employing contour bunds, terracing and check dams to minimize runoff and enhance water retention. Despite these strategies, challenges persist, including insufficient funding, limited institutional capacity, and inadequate climate information. Water quality becomes affected, and climate change becomes a big bane, like when the pH goes down due to acid rain in tank irrigation systems, which impacts soil health and crop productivity. These hazards are countered by lime treatment for acidity neutralisation, buffer zone strategies facilitated with vegetative barriers to act as pollutants filters, and afforestation to reduce sulfur and nitrogen emissions. Several strategies and components are used to improve a tank irrigation system and make it more adaptable and sustainable. Furthermore, developing climate-resilient infrastructure, encouraging water-saving technologies such as precision irrigation, and enhancing climate information services for farmers are also required to address knowledge gaps. Government financial help may go into subsidies, grants, or rebates to motivate investment in resilience–building actions such as infrastructure development, water–saving technologies, and weather–resistant crops.